Analisis Penegakan Hukum Terhadap Tindak Pidana Kekerasan dalam Rumah Tangga - Lukman, Lutfiana; Moonti, Roy Marthen; Kadir, Yusrianto; Kasim, Muslim A. (Politika Progresif : Jurnal Hukum, Politik dan Humaniora, 2025)
Domestic Violence (DV) is a serious human rights violation, particularly affecting women as a vulnerable group. Gorontalo City has seen a significant rise in DV cases, reflecting weak prevention efforts and law enforcement. Although Law No. 23/2004 regulates the elimination of DV, its local implementation faces structural, cultural, and resource-related challenges. This study analyzes the effectiveness of DV law enforcement in Gorontalo and identifies key obstacles. Using an empirical juridical method with a qualitative approach, data were collected through field research, interviews with law enforcers, and document analysis. The findings reveal that despite procedural efforts, barriers such as low public legal awareness, partiality among officials, limited victim protection facilities, and patriarchal norms hinder effective enforcement. Law enforcement remains ineffective due to weak institutional synergy and victims’ reluctance to seek justice. The study recommends specialized training for law enforcers, strengthening integrated victim services, and intensive legal outreach to build a more responsive environment to DV issues.